1968
DOI: 10.1111/j.1939-0025.1968.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

A three-year posthospital follow-up of adolescent and adult schizophrenics.

Abstract: A follow-up of 81 well-educated, voluntary, intensively treated schizophrenic patients, divided into three groups according to age of first hospitalization, revealed that adolescents had the most unfavorable outcome, older adults the most favorable. Developmental, social, diagnostic, and psychometric predic tors of outcome are discussed, as well as theoretical and practical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 10 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…This included 17 children without unaffected siblings, leaving 93 affected children and 138 siblings available for analysis. The mean (14-2 (SD 4-1) years) and median (15-0 years) ages for children with ulcerative colitis were comparable with those of the group of unaffected siblings (6 5); 15 …”
Section: Appendixmentioning
confidence: 71%
“…This included 17 children without unaffected siblings, leaving 93 affected children and 138 siblings available for analysis. The mean (14-2 (SD 4-1) years) and median (15-0 years) ages for children with ulcerative colitis were comparable with those of the group of unaffected siblings (6 5); 15 …”
Section: Appendixmentioning
confidence: 71%
“…Offord and Cross (1971) and Offord (1974) found that early onset (late teens to early twenties) and increased periods of institutionalization in adult schizophrenics are directly related to lower childhood IQ and scholastic failure relative to these patients' siblings and normal control subjects. This finding may be related to the observation that certain preschizophrenics have childhood symptomatology suggestive of possible minimal brain damage (Belmont et al, 1964;Pollack, Levenstein, & Klein, 1968). In any event, reasoning that intelligence may serve as a modifying trait in persons predisposed to schizophrenia, Offord and Cross (1971) and Jones (1973) suggest that in a family predisposed to schizophrenia, the child with the lowest IQ is the most vulnerable to early and more frequent breakdowns.…”
Section: Clinical Correlatesmentioning
confidence: 91%
“…Lane & Albee (1966) found that the mean birthweight, recorded on birth certification, of 52 schizophrenic adults was significantly less than that of their 115 siblings. Pollack's group reported that nine schizophrenic patients whose mothers reported ' severe paranatal complications' were younger at first hospitalization and showed a poorer outcome than 43 patients without such backgrounds (Pollack & Greenberg, 1966;Pollack et al 1968). The same group found more OCs in a second series of 32 schizophrenic patients than in healthy siblings, although no significant difference in birthweight was seen (Woerner et al 1971(Woerner et al , 1973.…”
Section: Introductionmentioning
confidence: 99%